Century 21 accounting - Kenton E. Ross (South-Educational Pub., 2000)
This seventh edition continues to emphasize corporate accounting. The text integrates accounting practices and related computer skills to prepare advanced students for future employment. The instructional format includes frequent assessment and short units with reinforcement activities